Disparities in Total Hip Arthroplasty Versus Hemiarthroplasty in the Management of Geriatric Femoral Neck Fractures. (September 2017) - Dangelmajer, Sean; Yang, Arthur; Githens, Michael; Harris, Alex H. S.; Bishop, Julius A.
Introduction: Recent clinical evidence suggests that total hip arthroplasty (THA) provides improved clinical outcomes as compared to hemiarthroplasty (HA) for displaced femoral neck fractures in elderly individuals. However, THA is still utilized relatively infrequently. Few studies have evaluated the factors affecting utilization and the role socioeconomics plays in THA versus HA. Methods: In the United States, the National Inpatient Sample (NIS) database was used to identify patients treated surgically for femoral neck fracture, between 2009 and 2010. Patients were identified using International Classification of Diseases, Ninth Revision, codes for closed, transcervical femoral neck fractures and closed fractures at unspecified parts of the femoral neck. All candidate predictors of THA versus HA were entered into a multilevel mixed-effect regression model. Results: Older patient age, being Asian or Pacific Islander, and having Medicaid payer status were all associated with lower odds of receiving THA. Patients with private insurance including Health Maintenance organization (HMO) had higher odds of THA as did patients with other insurance. Odds of THA were significantly lower among patients in teaching hospitals and higher at hospitals with greater THA volume. Discussion: Ethnicity, payer status, hospital size, and institutional THA volume were all associated with the utilization of THA versus HA in the treatment of geriatric femoral neck fractures. Level of Evidence: Level III Retrospective Cohort study.